La Libia Precoloniale - Jerari, Mohammed (La Libia Nella Storia D'italia (1911-2011), 2015)

La Libia Vista Dall'italia. Appunti Storici Su Alcuni Scrittori - Labanca, Nicola (La Libia Nella Storia D'italia (1911-2011), 2015)

قراءة جديدة حول زاوية سيدي قناو / علي المقاني بجبل مطماطة - بوخشيم, النوري (التوطن والمجال الثقافة المادية في حوض المتوسط : أعمال ندوة قسم علم الآثار أفريل 2014, 2015)
Keywords: Archéologie -- Matmata

قراءة في بعض ملامح التعمير بقرية زمرتن بجبل مطماطة - بوخشيم, النوري (الجبل والسهل في حوض المتوسط. أعمال الندوة العلمية الدولية الرابعة (القيروان 5، 6 و7 ديسمبر 2011), 2015)
Keywords: Archéologie -- Matmata

‏حول قرية هداج بجبل مطماطة - بوخشيم, النوري (بحوث في التاريخ والجغرافيا والحضارة: أعمال مهداة إلى الأستاذين منيرة الرمادي وعبد الله الشريف = Etudes d'histoire, géographie et civilisation: Mélanges offerts aux professeurs Mounira Remadi Chapoutot et Abdallah Cherif, 2015)
Keywords: Matmata -- Histoire

Archaeological excavations at bahla fort and great mosque - Bakri, Sultan Saif al- (The archaeological heritage of Oman: proceedings of the symposium, September 7th 2012, UNESCO Headquarter, Paris, 2015)
Keywords: Archéologie -- Oman

Life and death in prehistoric oman: Insights from late neolithic and early bronze age funerary practices (4th - 3ed mill. BC) - Bortolini, Eugenio; Munoz, Olivia (The archaeological heritage of Oman: proceedings of the symposium, September 7th 2012, UNESCO Headquarter, Paris, 2015)
Keywords: Archéologie -- Oman

The beginning of copper metallurgy in oman - Giardino, Claudio (The archaeological heritage of Oman: proceedings of the symposium, September 7th 2012, UNESCO Headquarter, Paris, 2015)
Keywords: Archéologie -- Oman

Textual sources about magan and the countries of the "Lower Sea" - Glassner, Jean-Jacques (The archaeological heritage of Oman: proceedings of the symposium, September 7th 2012, UNESCO Headquarter, Paris, 2015)
Keywords: Archéologie -- Oman

Copper from oman in mesopotamia and the gulf: Chemical and isotopic studies - Hauptmann, Andreas (The archaeological heritage of Oman: proceedings of the symposium, September 7th 2012, UNESCO Headquarter, Paris, 2015)
Keywords: Archéologie -- Oman

The haft period in the oman peninsula: Cultural and economic changes - Jahwari, Nasser Said al- (The archaeological heritage of Oman: proceedings of the symposium, September 7th 2012, UNESCO Headquarter, Paris, 2015)
Keywords: Archéologie -- Oman

The archaeological heritage of oman. Exploration, conservation, restoration and public fruition - Lawati, Hassan Bin Mohammed Bin Ali al- (The archaeological heritage of Oman: proceedings of the symposium, September 7th 2012, UNESCO Headquarter, Paris, 2015)
Keywords: Archéologie -- Oman

The early oases of the hajar region - Orchard, Jocelyn; Orchard, Jeffery (The archaeological heritage of Oman: proceedings of the symposium, September 7th 2012, UNESCO Headquarter, Paris, 2015)
Keywords: Archéologie -- Oman

The UNESCO world heritage site of bat and al-ayn: Past, present, and future - Thornton, Christopher P.; Schmidt, Conrad (The archaeological heritage of Oman: proceedings of the symposium, September 7th 2012, UNESCO Headquarter, Paris, 2015)
Keywords: Archéologie -- Oman

Magan: Another heartland of bronze age civilization. Conquerors of the desert, conquerors of the ocean - Tosi, Maurizio (The archaeological heritage of Oman: proceedings of the symposium, September 7th 2012, UNESCO Headquarter, Paris, 2015)
Keywords: Archéologie -- Oman

The ibri/Selme hoard from al-Zahirah province - 30 years after - Yule, Paul A. (The archaeological heritage of Oman: proceedings of the symposium, September 7th 2012, UNESCO Headquarter, Paris, 2015)
Keywords: Archéologie -- Oman

Circulations transsahariennes et pratiques musicales : quelques pistes pour l'éthnomusicologie - Belhachemi, Faouzia (Arts et musiques tunisiens, dimensions arabo-musulmanes, africaines et méditerranéennes, L'empreinte Maghrébine, 2e session, 13-19 Avril 2015, 2015)
Keywords: Musique -- Djerba

Le Gûgay, genre de vièle tunisienne - Gouja, Zouhair (Arts et musiques tunisiens, dimensions arabo-musulmanes, africaines et méditerranéennes, L'empreinte Maghrébine, 2e session, 13-19 Avril 2015, 2015)
Keywords: Musique -- Djerba

De l'art mudéjar à la théologie de la libération: influences de l'occident musulman sur l'Amérique latine via la péninsule ibérique - Rey, Pierre-Philippe (Arts et musiques tunisiens, dimensions arabo-musulmanes, africaines et méditerranéennes, L'empreinte Maghrébine, 2e session, 13-19 Avril 2015, 2015)

خواطر حول الهوية الموسيقية التونيسية - قوجة, محمد (الموسيقى والفنون التونسية في مجالها العربي الإسلامي والإفريقي والمتوسطي، البصمة المغاربية : الدورة الثانية، أيام 13-19 أفريل 2015, 2015)

من اجل قراءة نقدية لمفهوم التراث الموسيقي في علاقته بجدلية المحافظة والاستحداث - قوجة, محمد (الموسيقى والفنون التونسية في مجالها العربي الإسلامي والإفريقي والمتوسطي، البصمة المغاربية : الدورة الثانية، أيام 13-19 أفريل 2015, 2015)

Migration, mémoire et tourisme, l'exemple des Mozabites - Abderrezek, Kaouther (Le tourisme de mémoire: un atout pour les collectivités territoriales ?, 2015)
Keywords: Emigration -- Mzab -- Algérie

Traces of an Indian Community in the City of Sumhuram, Oman: Investigation of Materials Found during Excavations - Lischi, Silvia (Invisible cultures: historical and archaeological perspectives, 2015)
Keywords: Archéologie -- Oman

Les caractéristiques de l'architecture religieuse Ibâdite : étude des mosquées dans la vallée du Mzab, à Djerba, au Djebel Nafusa et dans les piémonts omanais - Benkari, Naïma (Le Patrimoine architectural de l'Église Orthodoxe d'Antioche: perspectives comparatives avec les autres groupes religieux du Moyen-Orient et des régions limitrophes, 2015)
Keywords: Architecture -- Mzab

التربية الإسلامية في سير الإباضية أبو عبد الله محمد بن بكر الفرسطائي أنموذجا - بن سعدون, المنير بن عبد الحميد (الندوة الدولية العلمية حول كتب السير الإباضية 31 أكتوبر-2 نوفمبر 2014م, 2015)
Keywords: Furṣuṭāʾī, Muḥammad b. Bakr

الدرجيني مؤرخ بالمهارة والاكتساب أديب بالفطرة - الباروني, سناء مهني (الندوة الدولية العلمية حول كتب السير الإباضية 31 أكتوبر-2 نوفمبر 2014م, 2015)

السير الإباضية عند المستشرقين - بن معاد, منجي بن علي (الندوة الدولية العلمية حول كتب السير الإباضية 31 أكتوبر-2 نوفمبر 2014م, 2015)

البرادي أبو الفضل أبو القاسم - الجعبيري, فرحات بن علي (الندوة الدولية العلمية حول كتب السير الإباضية 31 أكتوبر-2 نوفمبر 2014م, 2015)
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-

السير الإباضية بين المشارقة والمغاربة - السيابي, أحمد بن سعود (الندوة الدولية العلمية حول كتب السير الإباضية 31 أكتوبر-2 نوفمبر 2014م, 2015)

كتب السير والطبقات عند الإباضي الدرجيني وكتابه طبقات المشائخ أنموذجا - البجاحي, عيسى امحمد (الندوة الدولية العلمية حول كتب السير الإباضية 31 أكتوبر-2 نوفمبر 2014م, 2015)
Keywords: Prosopographie -- Afrique du Nord

سيرة لبعض فقهاء المسلمين إلى الإمام الصات بن مالك - مصلح, أحمد بن مهني (الندوة الدولية العلمية حول كتب السير الإباضية 31 أكتوبر-2 نوفمبر 2014م, 2015)

سيرة أبي الخطاب عند الأعلى المعافري من خلال كتاب السيرة وأخبار الأئمة لأبي زكرياء يحيى بن أبي بكر الوارجلاني - الطرابلسي, حنان (الندوة الدولية العلمية حول كتب السير الإباضية 31 أكتوبر-2 نوفمبر 2014م, 2015)
Keywords: Biographies

البعد الخطابي السلطوي (قراءة في كتاب تحفة الأعيان) - السليماني, عيسى بن محمد (الندوة الدولية العلمية حول كتب السير الإباضية 31 أكتوبر-2 نوفمبر 2014م, 2015)

السيرات في المجتمع الإباضي بوادي مزاب - بحاز, إبراهيم بن بكير (الندوة الدولية العلمية حول كتب السير الإباضية 31 أكتوبر-2 نوفمبر 2014م, 2015)

خصائص السير العمانية - بوحجام, محمد بن قاسم ناصر (الندوة الدولية العلمية حول كتب السير الإباضية 31 أكتوبر-2 نوفمبر 2014م, 2015)

منهجية الشيخ محمد بن عبد اللهبن مداد الناعبي في كتابه سيرته المعروفة بسيرة العلماء - الشعيبية, بدرية بنت علي (الندوة الدولية العلمية حول كتب السير الإباضية 31 أكتوبر-2 نوفمبر 2014م, 2015)

الإسناد الديني (نسب الدين) عند الإباضية بالمغرب - الحاج موسى, بشير بن موسى (الندوة الدولية العلمية حول كتب السير الإباضية 31 أكتوبر-2 نوفمبر 2014م, 2015)

الأبعاد الحضارية لسيرة حلقة العزابة في ق5هـ - كروم, أحمد بن حمو; بازين, عمر بن أحمد (الندوة الدولية العلمية حول كتب السير الإباضية 31 أكتوبر-2 نوفمبر 2014م, 2015)

المرأة في السير الإباضية - الأسود, أحمد (الندوة الدولية العلمية حول كتب السير الإباضية 31 أكتوبر-2 نوفمبر 2014م, 2015)

أضواء على بعض السير المغاربية الإباضية (سير الوسياني والبغطوري نموذجا) - بوعصبانة, عمر بن لقمان (الندوة الدولية العلمية حول كتب السير الإباضية 31 أكتوبر-2 نوفمبر 2014م, 2015)
Keywords: Prosopographie -- Afrique du Nord

مدخل نظري إلى الأنتروبولوجيا التأويلية وطرائف استثمارها في فهم الأدبيات الإباضية - بوفريخة, أسامة (الندوة الدولية العلمية حول كتب السير الإباضية 31 أكتوبر-2 نوفمبر 2014م, 2015)

الشيخ سليمان بن ناصر الإسماعيلي وعلاقته بكتاب السير والجوابات بمكتبة السيد محمد بن أحمد البوسعيدي بسلطنة عمان - باحامد, إدريس بن بابه (الندوة الدولية العلمية حول كتب السير الإباضية 31 أكتوبر-2 نوفمبر 2014م, 2015)

الأخلاق والقيم في السير الإباضية كتاب طبقات المشايخ بالمغرب للدرجيني نموذجا - حاج أمحمد, يحيى بن بهون (الندوة الدولية العلمية حول كتب السير الإباضية 31 أكتوبر-2 نوفمبر 2014م, 2015)

دولة الإمامة من خلال سيرة العلامة المنير بن النير الجعلاني العماني - الندابى, ناصر بن على بن سالم (الندوة الدولية العلمية حول كتب السير الإباضية 31 أكتوبر-2 نوفمبر 2014م, 2015)

Ancient place names in the Adrar n Infusen. A field study in Kabaw - Buzakhar, Madghis; Buzakhar, Mazigh (La Lingua nella Vita e la vita della lingua : Itinerari e percorsi degli studi berberi. Miscellanea per il Centenario di studi berberi a "L'orientale" di Napoi Scritti in onore di Francesco Beguinot, 2015)
Keywords: Djebel Nefousa -- Histoire

La permanence du christianisme au Maghreb : l’apport problématique des sources latines - Valérian, Dominique (Islamisation et arabisation de l’Occident musulman médiéval (viie-xiie siècle), 2015)

L’islamisation du maghreb central (viie-xie siècle) - Amara, Allaoua (Islamisation et arabisation de l’Occident musulman médiéval (viie-xiie siècle), 2015)

Francesco Beguinot (1879-1953) et les études berbères à Naples - Di Tolla, Anna Maria (La Lingua nella Vita e la vita della lingua : Itinerari e percorsi degli studi berberi. Miscellanea per il Centenario di studi berberi a "L'orientale" di Napoi Scritti in onore di Francesco Beguinot, 2015)
Keywords: Orientalisme -- Italie

حول ظهور قبائل دمر وزنزفة و مطماطة بجنوب شرق إفريقيا - الباهي, أحمد (بحوث في التاريخ والجغرافيا والحضارة أعمال مهداة إلى الأستاذين منيرة الرمادي شابوطو وعبد الله الشريف, 2015)

Sorcellerie berbère, antiques talismans et saints protecteurs au Maghreb médiéval - Coulon, Jean-Charles (Dynamiques religieuses et territoires du sacré au Maghreb médiéval: éléments d'enquête, 2015)
Keywords: Occultisme -- Afrique du Nord

Some Observations on the Anti-Donatist Legislation - Marone, Paola (The uniquely African controversy: studies on Donatist Christianity, 2015)
Keywords: Donatisme

Sur les mots et phrases en berbère ancien contenus dans l’ouvrage de Wisyānī (VIe H. / XIIe siècle) : Éléments d’une recherche en cours - Ould-Braham, Ouahmi (La Lingua nella Vita e la vita della lingua : Itinerari e percorsi degli studi berberi. Miscellanea per il Centenario di studi berberi a "L'orientale" di Napoi Scritti in onore di Francesco Beguinot, 2015)
Keywords: Linguistique; Prosopographie -- Djebel Nefousa

Espaces et figures du sacré dans le bassin d'Ouargla. L'histoire d'un lieu de mémoire de l'ibadisme médiéval - Aillet, Cyrille (Dynamiques religieuses et territoires du sacré au Maghreb médiéval: éléments d'enquête, 2015)
Keywords: Ibadisme -- Ouargla

Des communautés ibadites au Kairouan et dans le Sāḥil jusqu'au XIIe siècle ? un nouvel examen des sources - Prevost, Virginie (Dynamiques religieuses et territoires du sacré au Maghreb médiéval: éléments d'enquête, 2015)

Autour d’un glossaire arabo-berbère du Moyen-Age (‘Dialecte du Djebel Nefoussa’) - Naït-Zerrad, Kamal (La Lingua nella Vita e la vita della lingua : Itinerari e percorsi degli studi berberi. Miscellanea per il Centenario di studi berberi a "L'orientale" di Napoi Scritti in onore di Francesco Beguinot, 2015)
Keywords: Linguistique -- Djebel Nefousa

Malāmiḥ ʿAṣr al-Imām Muḥammad b. ʿAlī al-Qalaʿī. Al-Ḥayāt al-Siyāsiyya wa’l-Fikriyya fī ‘l-Qarn al-sādis al-Hijrī - al-thānī ʿashar al-Mīlādī - ʿUmarī, Saʿīd b. Khālid (al-Imām al-Qalʻī: ḥaṣād nadwat Min Aʻlāminā, al-Ithnayn 27 Ṣafar 1434 H al-muwāfiq 30 Dīsimbir 2012 M, 2015)

Muḥammad b. ʿAlī b. al-Ḥasan b. ʿAlī b. Abī ʿAlī al-Qalaʿī: Sīratuhu wa-Ma’āthiruhu - Ṣayʿarī, ʿUmar b. ʿAbdallāh Maḥrūs (al-Imām al-Qalʻī: ḥaṣād nadwat Min Aʻlāminā, al-Ithnayn 27 Ṣafar 1434 H al-muwāfiq 30 Dīsimbir 2012 M, 2015)

al-Makāna al-ʿIlmiyya li’l-Imām Muḥammad b. ʿAlī al-Qalaʿī - Bāʿumar, Ḥusayn b. Aḥmad b. ʿAlawī al-Dhīb (al-Imām al-Qalʻī: ḥaṣād nadwat Min Aʻlāminā, al-Ithnayn 27 Ṣafar 1434 H al-muwāfiq 30 Dīsimbir 2012 M, 2015)

Manhaj al-Imām Abī ʿAbdallāh Muḥammad b. ʿAlī al-Qalaʿī fī ‘l-Ta’līf: Tahdhīb al-Riyāsa wa-Tartīb al-Siyāsa Unmūdhajan - Bālkhayr, Aḥmad b. ʿAbd al-Raḥmān (al-Imām al-Qalʻī: ḥaṣād nadwat Min Aʻlāminā, al-Ithnayn 27 Ṣafar 1434 H al-muwāfiq 30 Dīsimbir 2012 M, 2015)

al-ʿAllāma Ibr. b. Saʿīd al-ʿIbrī Shāʿiran wa-Adīban - Salīmī, Maḥmūd b. Mubārak al-; Salīmiyya, Munà bint Ḥabrās al- (al-ʿAllāma Ibr. b. Saʿīd al-ʿIbrī: Ḥayātuhu wa-Fikaruhu, 2015)
Keywords: Poésie -- Oman

al-Simāt al-Manhajiyya li-Fiqh al-Shaykh Ibr. b. Saʿīd al-ʿIbrī - Saʿdī, Fahd b. ʿAlī b. Hāshil al- (al-ʿAllāma Ibr. b. Saʿīd al-ʿIbrī: Ḥayātuhu wa-Fikaruhu, 2015)
Keywords: Fiqh

al-Taʿrīf bi-Mawsūʿat al-Āthār al-ʿIlmiyya li’l-Shaykh al-ʿAllāma al-Shaykh Ibr. b. Saʿīd al-ʿIbrī - ʿIbrī, ʿAlī b. Hilāl al- (al-ʿAllāma Ibr. b. Saʿīd al-ʿIbrī: Ḥayātuhu wa-Fikaruhu, 2015)

al-Manhaj al-Tārīkhī ʿinda ‘l-ʿAllāma Ibr. b. Saʿīd al-ʿIbrī fī Kitāb ‟Tabṣirat al-Muʿtabarīnˮ - ʿAysarī, Muḥammad b. ʿĀmir b. Sayf al- (al-ʿAllāma Ibr. b. Saʿīd al-ʿIbrī: Ḥayātuhu wa-Fikaruhu, 2015)

l’image des Berbères dans les sources ibadites - Ben Hassine, Boutheina (Géographie Historique du Maghreb antique et médiéval: état des lieux et perspectives de recherches: actes du premier colloque international du Laboratoire de Recherches "Occupation du sol, peuplement et modes de vie dans le Maghreb antique et médiéval", Sousse les 14, 15, 16 mars 2014, 2015)

دور الجمعيات الأهلية بليبيا في نشر الوعي البيئي : جمعية جبل نفوسة للتنمية بالأصابعة - وفاء, فطيمة يوسف; العجمي, أسامة جمعه علي (المؤتمر الثاني لعلوم البيئة, 2015)
العمل الأهلي سمة من سمات المجتمعات القديمة منها والحديثة التي تبدو أنها أكثر فاعلية. ويمارس من خلال نظم ولوائح وتشريعات وقوانين تسيره وتنظمه لتقديم خدمات للمجتمع. إلا أنه في ظل التحولات والتغيرات التي تمر بها البلاد العربية ولا سيما ليبيا يحتاج العمل الأهلي لزيادة في الدعم والتنسيق والترابط بين مؤسسات المجتمع المختلفة. وتهدف الدراسة إلى إبراز العمل الأهلي من خلال الجمعيات الأهلية وبيان دورها حيث تم التركيز على جمعية جبل نفوسة للتنمية باعتبارها من الجمعيات الرائدة في مجال خدمة البيئة وتنمية المجتمع، وما توليه من اهتمام بالجانب البيئي من توعية وتثقيف خلال جملة من البرامج والأنشطة البيئية. وتوصلت الدراسة إلى وجود تنوع في الأنشطة والبرامج التي تقوم بها الجمعية في حماية البيئة وتنمية الوعي البيئي ما بين أنشطة توعوية كالمحاضرات والندوات، وأنشطة علاجية كحملات التنظيف والتشجير، وأنشطة وقائية كإصدار مطبوعات ومطويات ومخاطبات.

Kharijites and Qarmatians: Islamic pre-Democratic Thought, a Political Theological Analysis - Demichelis, Marco (Religion and representation: islam and democracy, 2015)
Keywords: Kharijisme

Les manifestations de la croyance religieuse dans l’architecture ibadite: l’exemple de Djerba - Teghlet, Zouhair (Insularité, langue, mémoire, identité, 2015)
Keywords: Architecture -- Djerba; Jami al-Kabir, mosquée al- (Hachene, Djerba); Monuments -- Djerba

L’image du bon gouvernement et le façonnement d’une mémoire communautaire dans l’ibadisme maghrébin médiéval - Aillet, Cyrille (Apprendre, produire, se conduire : Le modèle au Moyen Âge, 2015)
Keywords: Gouvernance -- Ibadisme

Ibadi Jurisprudence: Responses to Modernity - Ghazal, Amal N. (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Fiqh

Ibāḍī Jurisprudence and the Law of the Sea - Abou-el-Wafa, Ahmed (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Droit maritime -- Oman; Fiqh

Water and the Law in Oman - Rohe, Mathias (Ibadi jurisprudence: origins, developments and cases, 2015)

The Built Environment in Ibadi Law of the 5th-6th Centuries H (11th-12th AD) - Othman, Abdulsattar (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Fiqh

A Matter of Limited Female Agency: Oman’s Personal Status Law and Ibadi Jurisprudence on Khulʿ and Other Forms of Divorce Initiated and/or Consented to by Women - Badry, Roswitha (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Fiqh -- Oman

Jewish Law in Ibāḍī Context—the Case of Levirate and Temporary Marriages. Some Remarks on Carsten Niebuhr’s Observations - Schreiner, Stefan (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Judaïsme -- Djerba

A Basis for Oman’s Religious Tolerance: A Review of the Late 19th and Early 20th Century Ibadi Jurisprudence of Nūr al-Dīn al-Sālimī from Oman and Muḥammad Aṭfayyash from North Africa Regarding Coexistence with Jews and Christians - Leonard, Douglas R. (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914); Tolérance religieuse -- Oman

Ibāḍī Scholars on Association and Dissociation, from the 10th to the 21st Century - Hoffman, Valerie J. (Ibadi jurisprudence: origins, developments and cases, 2015)

Omani Classical Poetry and Discourse Deviation - Hajri, Hilal al-; Balushi, Khalid al- (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Poésie -- Oman

The Portrait of the Ibāḍīs in the Works of Scholars of Mā warāʾ al-Nahr - Usmanov, Ibrokhim Sabirovitch (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Ibadisme -- Asie centrale

The Ibadi Communities in Muslim Sicily - Chiarelli, Leonard (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Ibadisme -- Sicile

Ibāḍism and Mālikism. Notes on Some Hitherto Unknown Manuscripts - Muranyi, Miklos (Ibadi jurisprudence: origins, developments and cases, 2015)

The Legal Responsa Attributed to Aflaḥ b. ʿAbd al-Wahhāb (208–58/823–72). A Preliminary Study - Aillet, Cyrille; Hassen, Mohamed (Ibadi jurisprudence: origins, developments and cases, 2015)

The Ibadiyya Doctrine in North Africa: The Example of the Rustamid State - Guendouz, Latifa (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Dynastie rustumide

On the Relationship between Islamic Jurisprudence and Theology: The North African Ibadism Case - Ech-Cheikh, Mohammed (Ibadi jurisprudence: origins, developments and cases, 2015)

Common Ibāḍī/Shīʿite Legacy: Examples From the Ritual Law - Modaressi, Hossein (Ibadi jurisprudence: origins, developments and cases, 2015)

The Concept of Ijtihād According to the Ibāḍī School of Jurisprudence - Bājū, Muṣṭafà b. Ṣāliḥ (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Ijtihad

The Roots of the Uṣūl al-Fiqh in the Ibāḍī Madhhab: A Comparison Between Abū Saʿīd al-Kudamī and Ibn Baraka - Ziaka, Angeliki (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Fiqh

The Development of Ibāḍī Jurisprudence in Oman in the 3rd/9th and 4th/10th Centuries: A Preliminary Study of Some Marriage Issues - Kondo, Yohei (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Fiqh -- Oman

Early Omani Siyar: Sin and Repentance in Ibāḍī Legal Theory - Radivilov, Danylo (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Fiqh -- Oman

Early Islamic Theological Influence in Jurisprudence. An Ibāḍī Perspective - Salimi, Abdulrahman al- (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Fiqh -- Ibadisme

The Ibāḍī Law of Inheritance: Preliminary Notes on the Formation of the Ibāḍī School - Cilardo, Agostino (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Fiqh

Takfīr Re-examined: Polemic and Ambiguity in the Sources on the Muḥakkima - Gaiser, Adam R. (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Kharijisme

Aqwāl Qatāda and the Shuʿaybiyya and Nukkār - Madelung, Wilferd (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Nukkarisme

Contextualizing.The Development of Ibadi Fiqh - Wilkinson, John Craven (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Fiqh

Obituary for Annie Higgins - Seymour-Jorn, Caroline (Ibadi theology: rereading sources and scholarly works, 2015)
Keywords: Biographies

Al-Sālimī and the Ibāḍī Theology: the Mashāriq Anwār al-‘Uqūl - Coppola, Anna Rita (Ibadi theology: rereading sources and scholarly works, 2015)
Keywords: Foi -- Traité -- 19e siècle

Un manuscrit inédit d’hérésiographie: le Mabḥath al-firaq (Recherche sur les sectes) du shaykh Aṭfayyish (m. 1914) - Bouchiba, Farid (Ibadi theology: rereading sources and scholarly works, 2015)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914)

Shaykh Muḥammad b. Yūsuf Aṭfayyish: sa contribution au développement de la pensée théologique Ibadite - Ouinten, Moustafa (Ibadi theology: rereading sources and scholarly works, 2015)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914); Coran -- Commentaires -- 19e siècle

Politics and Polemics. Ibāḍī Theology in North Africa in the Modern Period - Ghazal, Amal N. (Ibadi theology: rereading sources and scholarly works, 2015)
Keywords: Réformisme

Ibāḍī Values and Modern Islam - Higgins, Annie C. (Ibadi theology: rereading sources and scholarly works, 2015)

Refuting the Vision of God in Ibāḍī Theology - Hoffman, Valerie J. (Ibadi theology: rereading sources and scholarly works, 2015)

Slavery and Abolition in Ibāḍī Theology: the Thought, the Un-thought, the Unthinkable - Daddi Addoun, Yacine (Ibadi theology: rereading sources and scholarly works, 2015)
Keywords: Esclavage -- Ibadisme

Jihād and Kharijism: a Note - Amoretti, Biancamaria Scarcia (Ibadi theology: rereading sources and scholarly works, 2015)
Keywords: Kharijisme

The Theory of the Atom in the Ibāḍī, Ashʿarite and Muʽtazilite Schools - Ismāʿīlī, Aḥmad (Ibadi theology: rereading sources and scholarly works, 2015)

Anthropomorphism of the Divine as Metaphor in Early Ibāḍī Theology and Reformed Calvinism - Kondo, Yohei (Ibadi theology: rereading sources and scholarly works, 2015)

The Concepts of walāya, barā’a and wuqūf among the 2nd/8th–3rd/9th Centuries Ibāḍis - Kondo, Yohei (Ibadi theology: rereading sources and scholarly works, 2015)

The Theology of Human Actions: Imposing the Impossible. Al-taklīf and its Problems among the Ibāḍis - Dridi, Moez (Ibadi theology: rereading sources and scholarly works, 2015)

La notion de péché et le sort réservé à son auteur chez les ibāḍites des trois premiers siècles de l’hégire - Bendrissou, Moustafa (Ibadi theology: rereading sources and scholarly works, 2015)
Keywords: Foi -- thèmes et motifs

La théologie ibadite: genèse, évolution et enjeux - Jaabiri, Farhat; Mizouri, Laroussi (Ibadi theology: rereading sources and scholarly works, 2015)

Ibāḍism and the Creation of the Qur’ān - Salimi, Abdulrahman al- (Ibadi theology: rereading sources and scholarly works, 2015)

The Ibāḍiyya in Muslim Sicily: from the Muslim Conquest to Lucera? - Chiarelli, Leonard (Ibadi theology: rereading sources and scholarly works, 2015)
Keywords: Ibadisme -- Sicile

Ibāḍī ‘aqida-s in Berber - Di Tolla, Anna Maria (Ibadi theology: rereading sources and scholarly works, 2015)

Ignored Pages of the History of Ibāḍī Theology in North Africa during the Middle Ages. The Wājiz (Summary) of ʿAbd al-Kāfī and the Dalīl (Proof and Demonstration) of al-Warjlānī - Ech-Cheikh, Mohammed (Ibadi theology: rereading sources and scholarly works, 2015)

L’évolution de la théologie ibāḍīte maghrébine d’après une épître hérésiographique de la fin du Ve/Xe siècle - Amara, Allaoua (Ibadi theology: rereading sources and scholarly works, 2015)

Rereading Omani Siyar: Khālid b. Qaḥṭān - Radivilov, Danylo (Ibadi theology: rereading sources and scholarly works, 2015)

A Breviary of Faith and a Sectarian Memorial: a New Reading of Ibn Sallām’ Kitāb (3rd/9th Century) - Aillet, Cyrille (Ibadi theology: rereading sources and scholarly works, 2015)

The Reading of the Qur’ān, Sunna and Akhbār in Early Ibāḍī Sources - Busaidi, Saleh Ahmed al- (Ibadi theology: rereading sources and scholarly works, 2015)

Moderation and Extremism in Early Ibāḍī Thought - Wilkinson, John Craven (Ibadi theology: rereading sources and scholarly works, 2015)

Ibāḍī Identity and Imperial Politics in Early Islam - Ess, Josef van (Ibadi theology: rereading sources and scholarly works, 2015)

Early Ibāḍiyya in Comparative Perspective - Sayyid, Ridwan al- (Ibadi theology: rereading sources and scholarly works, 2015)

Ibāḍiyya and Mu‘tazila: Two Moderate Opposition Movements in Early Islam - Madelung, Wilferd (Ibadi theology: rereading sources and scholarly works, 2015)

Ibāḍī Studies in Naples. Rereading the Works of Last Century Italian Scholars - Francesca, Ersilia (Ibadi theology: rereading sources and scholarly works, 2015)
Keywords: Orientalisme -- Italie

Conoscenza scientifica e politica coloniale: Francesco Beguinot, l’impresa di Tripoli ed un progetto incompiuto di “Storia dei Berberi” (1911-1923) - Cresti, Federico (UniorPress, 2015)
Keywords: Orientalisme -- Italie

Due volte minoranza: i berberi ibaditi del jabal Nafusa nella visione coloniale - Cresti, Federico (Minoranze, pluralismo, stato nell'Africa mediterranea e nel Sahel, 2015)
Keywords: Berbérisme -- Djebel Nefousa

The Concept of sunna in the Ibāḍī School - Francesca, Ersilia (The Sunna and its Status in Islamic Law, 2015)
Keywords: Fiqh

Factionalism resurgent. The war in the Jabal Nafusa - Larcher, Wolfram; Labnouj, Ahmed (The Libyan Revolution and its aftermath, 2015)
Keywords: Vie politique -- Djebel Nefousa

Islands of Musical Memory: Performing Selihot According to the Codex Siftei Renanot in Al-Andalus, Djerba, Tripoli, and Israel from the Eleventh to the Twenty-first Centuries - Seroussi, Edwin (Musical exodus: Al-Andalus and its Jewish diasporas, 2015)
Keywords: Judaïsme -- Djerba; Musique -- Djerba

15 ae 1998, 282: A Case Study of Public Benefaction and Local Politics - Liu, Jinyu (Ancient Documents and their Contexts, 2015)
Keywords: Archéologie -- Djerba; C. Serviulius Diodorus

Hypothèses sur les techniques de pêche utilisées par les habitants du litoral nord-est de l'île de Djerba aux périodes punique et romaine, à partir des données archéologiques de Ghizène - Ben Tahar, Sami (Pêches méditerranéennes. Origines et mutations – Protohistoire-XXIe siècle, 2015)
Keywords: Archéologie -- Djerba